Comparison of Visual Transient Elastography and Shear Wave Elastography in Evaluating Liver Fibrosis in Patients with Chronic Liver Disease - Yang, Jiali (Int J Gen Med, 2021)
PURPOSE: This study investigated the effectiveness and feasibility of shear wave elastography ((sound touch elastography) STE and (shear wave elastography) SWE) and visual transient elastography (ViTE) in the noninvasive quantitative diagnosis of liver fibrosis in chronic liver disease (CLD). PATIENTS AND METHODS: A total of 106 patients with CLD underwent STE, SWE and ViTE elastography evaluation. The Young’s modulus of the three elastography was valuated and the diagnostic performances of the three techniques for liver fibrosis staging were compared. The area under the receiver operating curve (ROC) for the diagnosis of liver fibrosis was compared. The final diagnosis was based on the histological findings on the liver biopsy. RESULTS: 1) The correlation between ViTE and SWE, ViTE and STE, SWE and STE stiffness values were 0.72, 0.75, 0.75 (P<0.001). 2) The relationship between the results of each elastography technique and the stage of pathological liver fibrosis showed that the more severe the liver fibrosis was, the higher the stiffness value was (all P <0.001). 3) When the three elastography techniques were used to detect the degree of liver fibrosis in different pathological stages, there was no statistical difference in the stabilities of the boxplots. 4) The ROCs of the three elastography techniques (ViTE, SWE and STE) were 0.88, 0.91, 0.92, F0 vs F1-3; 0.84, 0.84, 0.84, F0-1 vs F2-4; 0.80, 0.79, 0.77, F0-2 vs F3-4; 0.80, 0.76, 0.71, F0-3 vs 4; the AUC of ViTE was higher than the AUC of STE in the identification of F4, but there were no statistical differences in the AUCs of other groups. CONCLUSION: ViTE has good stability for the liver stiffness measurement (LSM) and a high consistency with shear-wave elastography (SWE and STE). It is an effective tool for evaluating CLD, and its performance is comparable to SWE and STE. The combination of ViTE and STE can improve the specificity of disease diagnosis and do not add extra cost and may improve cost performance.